Tesla in Germany : the most powerful union confronts the most valuable car company - Kinkead, Gwen, 1951- (SAGE business cases., 2021)
Tesla, the world's most valuable car company, was poised to open a massive new plant in Germany. IG Metall, Germany's largest union, would not let Tesla flout German labor laws and traditions. How the confrontation should be resolved and how it would actually play out were very much at issue.